A Case Report on Ayurvedic Management of Dushta Vrana - Neethi Rajan; C.K Krishnan Nair (International Journal of Ayurveda and Pharma Research, 2021)
Dushta vrana is a commonly encountered problem in day-to-day practice. Contemporary progress in the field of surgery has reduced the incidence of wound infection to a great extent along with the use of antibiotics. But still the management of ulcer encounters many glitches. This case study discusses about a 58-year-old male patient who presented with a chronic non healing ulcer in the anterior aspect of the left ankle joint associated with pain, burning sensation, foul smelling and inflammation with no history of varicose veins. Patient was treated with Karaskara ksheera kashaya dhara followed by dressing with Jathyadi ghrta. Punarnavadi kashayam and Guggulupanchapala choornam was given internally for a period of 35days. Virechana with Avipathy Choornam was given once during the whole course of the treatment. Raktamokshana was done twice as Jaloukavacharana. In order to enhance the speedy recovery, traditional use of Kupeelu was considered. A highly potent drug among the Upavisha which is well known for properties like Vranahara, Soolahara, Kushtahara, Sothaghna etc. which augments the peripheral blood circulation, reduces pain, burning sensation and inflammation. The wound healed within a period of 35 days and got complete relief from pain, burning sensation and swelling. Thus, the patient was successfully treated with no complications.